2005
DOI: 10.1016/j.jneuroim.2005.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profile within the mouse central nervous system and activation of myelin-reactive T cells following murine coronavirus infection

Abstract: Multiple sclerosis (MS) is an autoimmune disease associated with environmental factors, possibly including several viruses such as the coronaviruses. Indeed, murine coronavirus (MHV) infection provides a well-known experimental model for MS studies. Intracerebral infection of C57BL/6 mice with MHV-A59 revealed that viral replication was efficient and that clearance of infectious virus occurred as soon as 7 days post-infection. Using cDNA arrays, analysis of gene expression profile in the brain revealed a modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Cytotoxic T lymphocytes attracted to the CNS during a murine coronavirus (MHV) infection need the help of the CD4 + population to be effective in clearing the virus from the CNS [46]. Moreover, we have recently demonstrated that MBP-reactive T cells were activated following MHV-A59 infection of the CNS [47]. Therefore, such CD4+ cells may also be essential to clear neuroinvasive HCoV [12] from the CNS and could react against myelin epitopes being exposed in significant concentrations after damage resulting from inflammation brought about by virus-mediated activation of glial cells, cytokines and nitric oxide [48].…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic T lymphocytes attracted to the CNS during a murine coronavirus (MHV) infection need the help of the CD4 + population to be effective in clearing the virus from the CNS [46]. Moreover, we have recently demonstrated that MBP-reactive T cells were activated following MHV-A59 infection of the CNS [47]. Therefore, such CD4+ cells may also be essential to clear neuroinvasive HCoV [12] from the CNS and could react against myelin epitopes being exposed in significant concentrations after damage resulting from inflammation brought about by virus-mediated activation of glial cells, cytokines and nitric oxide [48].…”
Section: Discussionmentioning
confidence: 99%
“…SR T cell accumulation within the CNS of infected mice was shown to peak in mice persistently infected with JHMV; yet, these cells were not retained arguing for minimal pathologic function. In addition, a recent report has suggested that infection with mouse hepatitis virus strain A59 promotes activation of autoreactive T cells specific to myelin basic protein, although the contributions of these cells to demyelination remain to be fully defined (25).…”
Section: Jhmv-induced Demyelinationmentioning
confidence: 99%
“…Whether a similar response occurs in MHV-infected mice and what the contributions are to demyelination are unknown at this time. A recent report has suggested that infection with MHV strain A59 promotes the activation of autoreactive T cells specific to myelin basic protein, although the contributions of these cells to demyelination are undefined [57].…”
Section: Jhmv-induced Demyelinationmentioning
confidence: 99%